2020
DOI: 10.1101/2020.03.20.999748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aggregated spatio-temporal division patterns emerge from reoccurring divisions of neural stem cells

Abstract: The regulation of quiescence and cell cycle entry is pivotal for the maintenance of stem cell populations. Regulatory mechanisms however are poorly understood. In particular it is unclear how the activity of single stem cells is coordinated within the population, or if cells divide in a purely random fashion. We addressed this issue by analyzing division events in an adult neural stem cell (NSC) population of the zebrafish telencephalon. Spatial statistics and mathematical modeling of over 80,000 NSCs in 36 br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…An "in vivo to modeling" cross-talk to study the spatiotemporal control of NSC decisions in the adult vertebrate brain Recent studies described a random spatial distribution of NSCs in S phase (Lupperger et al, 2018(Lupperger et al, , 2020, but alternative hypotheses such as local spatiotemporal regulation could not be excluded, and these studies were short-term (72 hours) and merged distinct neuroanatomical domains with reported differences in NSC activation frequencies (Dray et al, 2015). Analyzing the spatiotemporal dynamics of adult NSC populations is challenging: (i) it requires dynamic analyses of cell fate preserving NSC arrangements in their physiological niche, (ii) it involves recording jointly the behavior of each individual NSC and its neighbors, and (iii) it faces the extremely slow dynamics of NSC fate decisions, with quiescence times over months.…”
Section: Discussionmentioning
confidence: 99%
“…An "in vivo to modeling" cross-talk to study the spatiotemporal control of NSC decisions in the adult vertebrate brain Recent studies described a random spatial distribution of NSCs in S phase (Lupperger et al, 2018(Lupperger et al, , 2020, but alternative hypotheses such as local spatiotemporal regulation could not be excluded, and these studies were short-term (72 hours) and merged distinct neuroanatomical domains with reported differences in NSC activation frequencies (Dray et al, 2015). Analyzing the spatiotemporal dynamics of adult NSC populations is challenging: (i) it requires dynamic analyses of cell fate preserving NSC arrangements in their physiological niche, (ii) it involves recording jointly the behavior of each individual NSC and its neighbors, and (iii) it faces the extremely slow dynamics of NSC fate decisions, with quiescence times over months.…”
Section: Discussionmentioning
confidence: 99%